Analysis and Improvement of Dynamic Characteristic of High-speed Opener Cam Mechanism - Lei An; Suohuai Zhang; Wangxing Huang (Jixie chuandong)
As the main mechanism of the opener， the cam mechanism has detailed dynamic characteristics analysis， which will have important guiding significance for the dynamic performance improvement of the opener. The cam link and the camshaft are flexibly processed to create a multi-flexible body model of the cam mechanism， and the simulation results of the multi-rigid body model and the multi-flexible body model are compared. Based on the multi-flexible body model， the effects of input speed， damping coefficient， material parameters and structural parameters on the dynamic characteristic of the mechanism are analyzed. The results show that the simulation results of the multi-flexible model have guiding significance for the initial assembly of the opener. Reducing the cam thickness and increasing the damping can improve the dynamic characteristics of the mechanism and enable the opener to run at a faster speed. At the same time， using ANSYS to perform modal analysis on the cam with varying thickness， a basis for avoiding resonance and more comprehensive dynamic analysis is provided.